(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This article provides a detailed analysis of the impact of artificial intelligence (AI) on education. AI enhances the learning process by personalizing education, developing automated assessment systems, introducing virtual tutors, and expanding opportunities for remote learning, making modern education more efficient and accessible. Additionally, it assists teachers by reducing administrative tasks, allowing them to focus more on improving the learning experience. The article explores key areas of AI in education, its benefits, and future prospects. AI is becoming an integral part of the education system, offering innovative solutions such as personalized learning, big data analysis, speech recognition, and AI-powered assistants. Furthermore, the article discusses the potential future developments of AI and its growing role in shaping modern education.